Contextual factors experienced by mothers of children with special needs - Priscilla Matambanadzo; Anthea J. Rhoda (AOSIS, 2024)
Background: Caring for children with special needs places a burden on caregivers. The challenges experienced can be conceptualised as personal and environmental, as per the International Classification of Functioning, Disability and Health Framework (ICF). Objectives: Supported the caregiver experiences when caring for children with special needs and to conceptualise these needs in relation to the personal and environmental factors set out in the ICF. Method: A qualitative exploratory study was conducted, using purposive and snowball sampling. Semi-structured interviews were used to collect the data, which were then analysed thematically. Results: A total of six themes arose from the data. Two of these were related to personal factors: unemployment and caregiving, and marital uncertainty. The other four themes were related to environmental factors: family and caregiving factors, educational factors, health-systems challenges and perceptions of children with special needs. Conclusion: Caregivers of children with special needs experienced personal challenges, which resulted in feelings of isolation from family and society. They also faced environmental challenges in sectors such as education and health. Clinical implications: The management of children with special needs should include interventions within their environments to assist caregivers with their tasks. This could contribute to improved quality of life for both the caregivers and their children.